Analysing behavioural and socio-demographic factors and practices influencing Australian household food waste. (15th July 2021) - Ananda, Jayanath; Karunasena, Gamithri Gayana; Mitsis, Ann; Kansal, Monika; Pearson, David
Abstract: Household food waste occupies the lion share of the total food waste in developed countries and engenders substantial economic and environmental costs around the globe. It is a complex, multifaceted problem and is a key component of national food waste reduction plans. Although the factors that influence food waste are known, the magnitude of their relative effect on household food waste is not well understood. Using a large national-level data set ( n = 3756) and a count regression modelling approach, this paper analyses a range of behavioural and socio-demographic factors that influence household food waste in Australia. Findings reveal that food storage practices, leftover cooking skills, dining out behaviour, grocery spending and the frequency of grocery shopping are significant drivers of food waste at the household level. The study concludes that household food waste reduction strategies should focus on routinised food-related behaviours and initiatives on improving overall food management skills in order to reduce food waste effectively.